Intention to give birth in the health institutions and associated factors among women who gave birth in the last 6 months in Debre Berhan town, North Showa zone, Ethiopia: A community-based cross-sectional study - Amare, Nakachew Sewnet; Mekuriyaw, Abebayehu Melesew; Tesema, Getaye Worku; Ambaw, Yeshinat Lakew (Frontiers in Medicine, 2022)
Background Institutional delivery is a proxy for skilled birth attendance, which is an important intervention to reduce maternal and neonatal mortality. Even though institutional delivery has such importance, significant numbers of women in Ethiopia do not prefer to give birth in health institutions. This study aimed to assess women’s intention to give birth in health institutions and associated factors among women who gave birth in the last 6 months in Debre Berhan town, North Showa Zone, Ethiopia, 2020. Materials and methods A community-based cross-sectional study was conducted among women who gave birth in the last 6 months in Debre Berhan town from October 30 to November 30, 2020. A cluster sampling technique was used to select study participants. Pretested semi-structured interviewer-administered questionnaires were administered. A logistic regression model was performed, and adjusted odds ratios with a 95% confidence interval based on p < 0.05 were used to identify statistically significant variables. Result This study found that a total of 689 (88.8%) (95% CI: 86.6, 91%) respondents intended to deliver in the health facility. Being multiparous [AOR = 0.18 (95% CI: 0.08, 0.36)], having planned pregnancy [AOR = 3.1 (95% CI: 1.6, 5.9)], had no complications during previous delivery (AOR = 6.0 (95% CI: 3.5, 10.4)], and received respectful maternity care (RMC) during preceding delivery [AOD = 1.8 (95% CI: 1.05, 3.10)] are significantly associated with women’s intention to give birth in the health institution. Conclusion Childbirth is a special event that requires the safest place to save the lives of both the mother and newborn. In this study, the number of women who do not have the intention to give birth in the health institution is still high. Strategies to promote planned pregnancy, reduce complications during childbirth and provide RMC during childbirth should be designed and interventions should be implemented for all childbearing women.